The use of cannabinoids in dermatological pathophysiologies: a systematic review (Research, Society and Development, 2022)
This article is a systematic bibliographic review carried out in the period from October 25 to November 4, 2021 through electronic search in the databases of Google Scholar, Science Direct and PUBMED-NCBI-NIH to obtain more recent data, the guiding question of the research was: What is the importance of cannabinoids for the treatment of dermatological physiopathology? The eligibility criteria were selected articles from the last three years concerning cannabis, its cannabinoids and the treatment of dermatological lesions. The descriptors used were: Cannabis, Skin diseases and Cannabinoids verified in Health Science Descriptors (Decs) and Medical Subjec the adings (Mesh). The cross was succeeded using the boolean operator AND: "Cannabis" AND "Skindiseases" AND "Cannabinoids". Nine articles were elected, both analyzed qualitatively, through methodological reading. Even though medicinal herb is known for its psychological use, recent studies show that cannabinoids (Cbs) are actively involved in peripheral systems such as the innate, adaptive immune response. The endocannabinoid system is responsible for regulating several aspects of skin homeostasis such as proliferation, release and differentiation of inflammatory mediators. Therefore, it was possible to observe through the research that Cannabis sativa and its system present in the organism, has large participations for the control of several dermatological and non-dermatological diseases, however, studies are still quite recent and scarce regarding the effect of the herb in the dermatological area, however, already has great advances on its effectiveness.